2019
DOI: 10.1371/journal.ppat.1008049
|View full text |Cite
|
Sign up to set email alerts
|

The Plasmodium falciparum rhoptry bulb protein RAMA plays an essential role in rhoptry neck morphogenesis and host red blood cell invasion

Abstract: The malaria parasite Plasmodium falciparum invades, replicates within and destroys red blood cells in an asexual blood stage life cycle that is responsible for clinical disease and crucial for parasite propagation. Invasive malaria merozoites possess a characteristic apical complex of secretory organelles that are discharged in a tightly controlled and highly regulated order during merozoite egress and host cell invasion. The most prominent of these organelles, the rhoptries, are twinned, club-shaped structure… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
32
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(33 citation statements)
references
References 72 publications
1
32
0
Order By: Relevance
“…Since there was a defect in the discharge of the S804A mutant of RhopH3, we investigated if its localization was dependent on the phosphorylation of this site. To this end, immunofluorescence assays (IFAs) were performed on late schizonts/segmenters as RhopH3 is positioned in the rhoptries of merozoites at this stage for the release (8,19). RhopH3 was localized as puncta adjacent to rhoptry bulb protein RAP1 as expected in 3D7 parasites (Fig.…”
Section: Figmentioning
confidence: 81%
See 1 more Smart Citation
“…Since there was a defect in the discharge of the S804A mutant of RhopH3, we investigated if its localization was dependent on the phosphorylation of this site. To this end, immunofluorescence assays (IFAs) were performed on late schizonts/segmenters as RhopH3 is positioned in the rhoptries of merozoites at this stage for the release (8,19). RhopH3 was localized as puncta adjacent to rhoptry bulb protein RAP1 as expected in 3D7 parasites (Fig.…”
Section: Figmentioning
confidence: 81%
“…One is low-molecular-weight (LMW) complex, comprising RAMA, RAP1, RAP2, and RAP3. RAMA was recently demonstrated to play a key role in invasion (8), and RAP1 seems to be involved in trafficking of RAP2, which is essential for parasite survival (9). The other, high-molecular-weight (HMW) complex, consists of RhopH1/Clag, RhopH2, and RhopH3 (6,10,11).…”
mentioning
confidence: 99%
“…In addition, we previously reported that PfRON3 interacts with PfRON2 and PfRON4, but not with PfAMA1 ( Ito et al, 2011 ), suggesting that a portion of PfRON3 is involved in the formation of a RON complex (PfRON2, 3, and 4), but not in the moving junction complex (PfRON2, 4, 5, and PfAMA1) ( Ito et al, 2011 ). Taken together, the absence of PfRAMA affects the trafficking of its associated RONs, and this could potentially explain the abnormal rhoptry neck biogenesis as observed by Sherling et al, (2019) .…”
Section: Discussionmentioning
confidence: 97%
“…Recently the PfRAMA-PfRAP1 complex was also suggested as a cargo for the Plasmodium orthologue of sortilin ( Hallee et al, 2018b ). To further investigate the role of PfRAMA, Sherling et al, (2019) generated a PfRAMA conditional knockdown parasite line. Contrary to previous findings ( Topolska et al, 2004 ; Richard et al, 2009 ; Hallee et al, 2018b ), the PfRAMA knockdown parasites presented correct trafficking of PfRAP1 and PfRhopH3.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation